GI Motility Testing: Stomach, Small Bowel, and Colon. Issue 3 (March 2019) - Lee, Allen; Baker, Jason; Hasler, William L.
Abstract : Symptoms of abdominal pain, nausea, vomiting, bloating, abdominal distention, diarrhea, and constipation are common and may relate to abnormalities in gastrointestinal motility. There are a number of different options to study gastrointestinal motility. This article reviews novel and standard motility tests available in the stomach, small bowel, and colon. The indications for testing, technical details, advantages, and disadvantages of each test will be summarized.